2022
DOI: 10.3390/ijerph19148464
|View full text |Cite
|
Sign up to set email alerts
|

Eruption Pattern of Permanent Canines and Premolars in Polish Children

Abstract: Eruption is a complex and dynamic process determined by both genetic and epigenetic factors. This process involves a number of changes in the tissues surrounding the tooth and in tooth morphology. The aim of this study was to analyze the eruption sequence of permanent canines and premolars on the basis of pantomographic images. The study material consisted of 300 digital pantomographic images of children in the developmental period. The study group consisted of 165 boys and 135 girls. Images of patients of Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The paper presents a method for evaluating the position of the second premolar’s bud based on the author’s parameters. This work is a continuation of earlier studies describing the analysis of radiographs to assess the pattern of eruption of canines and premolars [ 8 ].…”
Section: Introductionmentioning
confidence: 80%
“…The paper presents a method for evaluating the position of the second premolar’s bud based on the author’s parameters. This work is a continuation of earlier studies describing the analysis of radiographs to assess the pattern of eruption of canines and premolars [ 8 ].…”
Section: Introductionmentioning
confidence: 80%
“…To avoid cases with accelerated eruption of the premolars, a panoramic x-ray confirmed that less than two-thirds of the roots were completed, and the successors were covered by bone. (22) Furthermore, according to Cieślińska K et al (33), during the intraosseous stage, the tooth moves at a rate of 1-10 µm per day which approximately will take 1 mm of bone to resorb in 4 to 5 months. Hence, bone covering over the crown of unerupted successors together with the determined stage of root development indicated the need for a space maintainer.…”
Section: Discussionmentioning
confidence: 99%
“…Для правильного співвідношення перших постійних молярів має значення попереднє співвідношення других тимчасових молярів. На правильне формування малого ключа оклюзії має значення послідовність прорізування постійних ікл та перших премолярів [10].…”
Section: вступunclassified
“…Перш за все для кваліфікованої ортодонтичної допомоги лікар повинен провести комплексну діагностику із застосуванням додаткових методів обстеження, як доповнення до клінічних даних. Для оцінки умов та стану розвитку зубів і опорних структур серед рентгенологічних методів, окрім ортопантомографії (ОПТГ) в сучасній ортодонтії широко застосовується цефалометрія, конусно-променева комп'ютерна томографія та інші методи для деталізації діагностики зубощелепних аномалій (ЗЩА) [10,11,19]. Саме рентгенологічні методи дослідження мають велике значення при виборі стратегії лікування адентії зубів.…”
Section: вступunclassified